2017
DOI: 10.1039/c7an00337d
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydration in living cells probed by Fourier transform infrared (FT-IR) spectroscopic imaging

Abstract: An application of disrelation mapping to Fourier transform infrared (FT-IR) spectroscopic imaging datasets is provided to reveal different H-bonded water species within a mammalian cell. 2D correlation analysis revealed a disrelation peak at (3420 cm, 3220 cm), showing the existence of a specific water band at around 3220 cm whose variation of absorbance did not follow the trend of water molecules with a well-coordinated H-bonding network. Disrelation maps constructed with disrelation intensities between (3420… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…In particular, a stringent test for the assessment of the spatial resolution achieved in FTIR spectroscopic imaging in both ATR and transmission modes has been presented and it has been demonstrated that the true spatial resolution is much lower than what is expected from the projected pixel size, which is often used, albeit incorrectly, as a value for spatial resolution. [103,105,108] Recently micro ATR-FTIR spectroscopic images of living cells have been analysed with disrelation mapping which allowed differentiating molecular states of water as well as studying hydration of proteins within living cells (Figure 4) [112]. he most recent developments in the area of FTIR spectroscopic imaging have been reviewed, where the current state of the art is summarised in detail.…”
Section: Ex-vivo-spectroscopic Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a stringent test for the assessment of the spatial resolution achieved in FTIR spectroscopic imaging in both ATR and transmission modes has been presented and it has been demonstrated that the true spatial resolution is much lower than what is expected from the projected pixel size, which is often used, albeit incorrectly, as a value for spatial resolution. [103,105,108] Recently micro ATR-FTIR spectroscopic images of living cells have been analysed with disrelation mapping which allowed differentiating molecular states of water as well as studying hydration of proteins within living cells (Figure 4) [112]. he most recent developments in the area of FTIR spectroscopic imaging have been reviewed, where the current state of the art is summarised in detail.…”
Section: Ex-vivo-spectroscopic Histopathologymentioning
confidence: 99%
“…[106,108,[113][114][115][116] Notably, Kimber and Kazarian specifically highlight improvements in spatial resolution and spectral quality through the use of novel added lenses and computational algorithms, as well as quantum cascade laser imaging systems, which offer advantages over traditional Fourier transform infrared systems with respect to the speed of acquisition and field of view [117]. [112] In the case of infrared spectral pathology (using either FTIR or QCL microscopes), there are technological challenges associated with the most appropriate substrate to use. The obvious choice, from the spectroscopists point of view, is to use an infrared transparent substrate such as CaF2 or BaF2, both of which also happen to be transparent in the visible, and contribute minimally to Raman spectra in the regions of interest for biological samples, and are therefore ideal for microscopy applications.…”
Section: Ex-vivo-spectroscopic Histopathologymentioning
confidence: 99%
“…Micro ATR-FTIR spectroscopic imaging has previously been used to investigate protein crystallisation [118], and aggregates in live cells [119], as well as to probe protein hydration in living cells [120]. Terahertz time-domain spectroscopy (THz-TDS) in the far IR region was used to investigate BSA protein solution at pHs ranging from 2.5-10, this paper found different conformations of BSA have varying impact on the dynamics of surrounding water molecules [121].…”
Section: Atr-ftir Spectroscopic Imaging Applied To Biopharmaceuticalsmentioning
confidence: 99%
“…Jiang and Rieppo 66 FT-IR imaging Biomedical (cartilage) 2D-COS, synchronous, asynchronous Marcott at al. 67 AFM-IR line scan Polymers (PHA), biomedical (bone) 2D-COS, synchronous, asynchronous Shinzawa et al 27 FT-IR imaging Biomedical (protein hydration in living cells)…”
Section: Author(s) Year Of Publication Analytical Technique Field Ofmentioning
confidence: 99%